A 44-to-60GHz, 9.7dBm P1dB, 7.1% PAE power amplifier with 2D distributed power combining by metamaterial-based zero-phase-shifter in 65nm CMOS - Fei, Wei (2013)
With the use of metamaterial based zero-phase-shifter, a 2D distributed power combining network is developed to provide distributed amplification and power combining simultaneously. Measured results show that the fabricated PA has 8.3dB gain, 7.1% PAE, and 9.7dBm P1dB with 16GHz bandwidth (44 to 60GHz).